Selecting the Right Technique for the Treatment of Submental Adiposity - Jones, Evan A.; Sturm, Angela (Facial Plastic Surgery, 2025)
This study focuses on interventions to improve the contour of the submentum. Various therapies for the submentum are available to the conscientious provider. To partner with patients effectively in today's aesthetic landscape, a provider must be well-versed in both surgical and minimally invasive techniques. This study aids decision-making and provides therapeutic options for a diverse patient population.Given the wide array of options for treating the submentum, this study differentiates based on invasiveness. Transcutaneous therapies include cryolipolysis, ultrasound, microwave, and laser. Percutaneous treatments include Kybella or enzymatic mixture injection and transcutaneous energy delivery. Liposuction with or without adjunctive treatments and deep neck lifts are the subcutaneous and structural options.Submental interventions, whether percutaneous, transcutaneous, or subcutaneous, amplify the natural characteristics and beauty of the patient. Aligning the proper technique with the proper patient is the mark of a perceptive surgeon who accounts for underlying anatomy and treatment goals.
Keywords: submental adiposity; double chin; radiofrequency; liposuction; neck lift